The Development of Relational Reasoning in South Korean Elementary and Middle-School Students: A Cross-Sectional Investigation - Chae, Soo Eun; Alexander, Patricia A. (Frontiers in Psychology, 2021)
Relational reasoning is a higher-order executive function that involves the ability to perceive meaningful patterns within a body of seemingly unrelated information. The ability of 749 fourth, sixth, eighth, and tenth graders to identify meaningful patterns in relational reasoning was investigated. This general cognitive ability was assessed by means of the Test of Relational Reasoning-Junior (TORRjr), a 32-item test organized into four 8-item scales that measures analogical, anomalous, antinomous, and antithetical reasoning, respectively. Students’ performance on the TORRjr was analyzed using non-parametric median-based analyses, confirmatory factor analysis, and measurement invariance test. The results indicated an asymptotic development pattern in overall RR across the grades. In comparison to analogy and anomaly, antinomy and antithesis scores were more fully developed by eighth grade and that level of performance was maintained in tenth grade. It was also determined that the measurement did not seem to vary by gender. The measurement was viable for the Korean samples up to approximately 15 years old. The significance of these findings for research and instructional practice are discussed.